The Effect of Macroeconomic Variables on the Capital Structure Decisions of Indian Firms: A Vector Error Correction Model/ Vector Autoregressive Approach - Khanna, Sakshi; Srivastava, Amit; Medury, Yajulu (International Journal of Economics and Financial Issues, 2015)
This paper sheds light on how the macroeconomic variables affect the capital structure decisions in context to the Equity Market Timing Theory, for the firms of an emerging economy- India. The analysis is done through analytical and causal research design using Vector Error Correction Model / Vector Autoregressive Model. Further, the effect is also analyzed when the firms are categorised into the varied sectors of economy- primary, secondary and tertiary. The period for the study is from the year 1992-2013. The results show that changes in macroeconomic environment cause changes in the firm’s choice of finance both in long run as well as in short run. The analysis shows that for primary sector firms, leverage is pro-cyclical; secondary sector firms imply a counter-cyclical leverage and for tertiary sector firms equity is pro-cyclical. Therefore, the managers must identify the windows of opportunity depending upon the sector to which the firms belong to. Keywords: Capital structure decisions; Equity Market Timing Theory; VECM/VAR; Macroeconomic variables JEL Classifications: E00; G3; G10; G30; G32